Mild Clinical Course of Severe Fever with Thrombocytopenia Syndrome Virus Infection in an Elderly Japanese Patient - Yuko Ohagi; Shinobu Tamura; Chiaki Nakamoto; Hiromichi Nakamoto; Masayuki Saijo; Masayuki Shimojima; Yoshio Nakano; Tokuzo Fujimoto (Case Reports in Infectious Diseases)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious and hemorrhagic disease recently described in China and western Japan. A 71-year-old healthy Japanese woman noticed a tick biting her after harvesting in an orchard and removed it herself. She developed diarrhea, anorexia, and chills eight days later. Because these symptoms continued, she visited a primary care physician 6 days after the onset. Laboratory data revealed thrombocytopenia, leukocytopenia, and elevated liver enzymes. She was then referred to our hospital. Although not completely fulfilling the diagnostic criteria used in a retrospective study in Japan, SFTS was suspected, and we detected SFTS virus in the patient’s blood using RT-PCR. However, she recovered without intensive treatment and severe complications 13 days after the onset. In this report, we present a mild clinical course of SFTS virus infection in Japan in detail.